Intelligent contracts in the electronic commerce: a dialectic analysis - Sánchez Sánchez, Juan Diego (2022)
The paper details the theoretical and applicative structure of the smart contracts considering the correspondent performance, application, and epistemological bases, it also presents the element of the suspensive clause implicit in the confection of these contracts which determines the effectiveness of the instrument. It analyses the link to the auto executable asset practice which is managed by the contract itself, and defined previously by the partie. These concepts are linked to the electronic commerce, accomplishing as well the determination of the relationship between the smart contracts and the electronic commercial purchase. The factors of its application in the electronical business are defined, under a contractual and computational application methodology.